Organization of nutrition and health promotion activities in the field of nutrition and physical activity in primary schools - Wolnicka, Katarzyna; Jaczewska-Schuetz, Joanna (Polish Journal of Public Health, 2012)
Introduction. The organization of nutrition and physical activity at school is an important element which influences the health of the student’s development and disposition to learn.Aim. The study was to evaluate the organization of the nutrition and health promotion activities in the field of nutrition and physical activity carried out in primary schools.Material and methods. The study was conducted in the school year 2010/2011 in 58 primary schools, urban and rural areas of five randomly selected regions. The evaluation was based on analysis of anonymous questionnaires among school principals regarding the organization of nutrition in schools, and programs / preventive actions related to the improvement of nutrition and physical activity among children and adolescents in these schools.Results. About 40.8% of students eat meals at school among the schools offering school lunches, including 38.5% in urban schools and slightly more – 42.4% in rural schools. Most schools (87.7%) are carrying out programs / activities related to the improvement of nutrition and physical activity, including 93.5% of urban schools and 80.8% of rural schools. Among the directors of schools in which there are shops, 80.5% declared that the school introduced some restrictions but in small range. It was found that in 42.9% of schools there are food and beverage advertisements. Participation in the extra-curricular sports activities organized by these school is declared by 36.6% of the students.Conclusions. In Poland the problem of nutrition in schools is not yet adequately resolved for many reasons, including organizational and financial ones. However, the increasing involvement of schools in educational activities related to the improvement of nutrition and physical activity among children and adolescents by conducting numerous activities and health promotion programs was found.